Navigating the uncommon: Goblet cell adenocarcinoma of appendix with brief review of literature - Trivedi, Uttapalla Laxmi; Das, Mayurakshi; Sekaran, Anuradha; Mathur, Siddhant; Rao, G V (Indian Journal of Case Reports, 2024)
Goblet cell adenocarcinoma (GCA) is a rare gastrointestinal malignancy with biological behavior intermediate between well-differentiated neuroendocrine tumor and adenocarcinoma. A succinct description of GCA has been made in the 5th edition of the World Health Organization classification of Digestive system tumors, after being decamped from the carcinoid group. Here, we present the case of a 44-year-old male, who presented with pain and abdominal distension and was found to have ileal stricture and subsequently underwent ileocecal resection. Histopathological examination revealed wall of the appendix infiltrated by a tumor, arranged predominantly in tubules (70%) and composed of goblet-like mucinous cells. Focal high-grade component (30%) of signet ring cells noted. Immunohistochemistry highlighted an amphicrine immunoprofile of diffuse CK20 and CDX2 immunopositivity and focal positivity for synaptophysin and chromogranin in the same tumor population. We also discuss the review of recent literature on cases of GCA and discuss its salient histological features, immunoprofile, and differential disgnoses.